Sub-atmospheric re-pressurization analysis of FRIB linac segment 2 cryogenic distribution system. Issue 1 (1st May 2022) - Howard, J; Knudsen, P; Hasan, N; Ganni, V
Abstract: The continuous wave heavy ion beam linear accelerator at FRIB consists of 46 cryo-modules, housing 324 superconducting radio-frequency (SRF) resonators and 69 superconducting solenoids. The three linear accelerator (Linac) segments, designated LS1 to LS3, are arranged in the shape of a paper clip, with 4 superconducting dipole magnets in the curved segments. The SRF resonators are operated at 2 K, requiring a sub-atmospheric helium pressure, and the superconducting magnets are operated at 4.5 K. The design of the cryogenic transfer-lines for these Linac segments is complex and contains multiple process lines. Namely, these are the primary (4.5 K) supply, and return, sub-atmospheric return, 35 K shield supply and 55 K shield return. The shield return encloses the other process lines, thermally intercepting the ambient temperature heat load. Testing was conducted on the re-pressurization and liquid levels of the 24 cryo-modules of LS2's 2 K system. System models were developed and then compared to the test data to characterize the static heat in-leak to the cryo-modules. Reasonable agreement was found between the validated models and preliminary measurements.